Islamic P2P Crowdfunding (IP2PC) Platform for the Development of Paddy Industry in Malaysia: An Operational Perspective - Hassan Azganin; Salina Kassim; Adam Auwal Saad (Journal of Islamic Finance, 2021)
Crowdfunding for agriculture provides a new social financing medium for agricultural financing, which is essential for promoting farmland revitalization and targeted poverty reduction among paddy farmers. The government sector and the social security system are unable to meet the demands of this growing systemic problem. In addition, paddy farmers in most developing countries strive to attain their basic needs and are among the most impoverished communities on the planet. This paper aims to present an Islamic P2P crowdfunding model as an alternative financing solution for paddy farmers in Malaysia. Besides, a standard operations procedure (SOP) has also been developed to ensure efficient management of the paddy project investments. This study uses document research methodology to analyze the related papers, journal articles and other published sources. Also, the literature on the financing gap faced by farmers and the crowdfunding solutions in agriculture has been reviewed critically and used to develop an alternative model. This study's findings reveal that Islamic P2P crowdfunding is expected to provide paddy farmers in Malaysia with an alternative source of funds to meet their liquidity constraints and finance their small businesses. The paper has also proposed an end-to-end operational procedure that can ensure the complete protection of different players' rights in the platform. The proposed model and SOPs can help policymakers and regulatory authorities to develop the required policies and create the needed agricultural crowdfunding regulations.